1986
DOI: 10.1038/bjc.1986.82
|View full text |Cite
|
Sign up to set email alerts
|

Neuron specific enolase expression in carcinoma of the lung

Abstract: Summary The value of neuron specific enolase (NSE) immunoreactivity as a marker for small cell lung cancer (SCLC) has been assessed using a monoclonal antibody (MCAB) against NSE. MCAB specificity was confirmed using purified enolase isoenzymes, sections of human brain, a panel of lung tumours, neuroendocrine and non-neuroendocrine tumours and normal tissues. Using this MCAB in radioimmunoassay and immunohistochemistry, NSE immunoreactivity was detected in all SCLC material examined. However, considerable reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In contrast, no y-enolase staining was found in British Journal of Cancer (1997) (Simpson et al, 1984;Vinores et al, 1984;Fukuda et al, 1989), and low levels of reactivity were detected in a cell line from a colon carcinoma (Reeve et al, 1986). As indicated above, we have detected ay-and yy-enolase in colon adenocarcinomas, although at a lower proportion than in normal tissue.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…In contrast, no y-enolase staining was found in British Journal of Cancer (1997) (Simpson et al, 1984;Vinores et al, 1984;Fukuda et al, 1989), and low levels of reactivity were detected in a cell line from a colon carcinoma (Reeve et al, 1986). As indicated above, we have detected ay-and yy-enolase in colon adenocarcinomas, although at a lower proportion than in normal tissue.…”
Section: Discussionmentioning
confidence: 44%
“…By immunoassay, the y-enolase subunit was detected in gastric and gut carcinoids (Tapia et al, 1981;Simpson et al, 1984;Nash et al, 1986), and in a cell line from a neuroendocrine tumour of colon (Reeve et al, 1986). In contrast, no y-enolase staining was found in British Journal of Cancer (1997) (Simpson et al, 1984;Vinores et al, 1984;Fukuda et al, 1989), and low levels of reactivity were detected in a cell line from a colon carcinoma (Reeve et al, 1986).…”
Section: Discussionmentioning
confidence: 98%
“…183 Neuron-specific enolase should not be used as a neuroendocrine marker because it lacks specificity. 184,185 There is a direct correlation between the degree of differentiation of the tumor (well-differentiated types, eg, carcinoid and pancreatic endocrine tumor, to poorly differentiated types, eg, small cell carcinoma) and the level of chromogranin A expression, as evidenced by the intensity of immunostaining and the fraction of positive tumor cells. Antibodies to chromogranin A, synaptophysin, or both, alone or in combination, will identify greater than 90% of neuroendocrine carcinomas, including small cell carcinomas, which correspond to ''poorly differentiated'' neuroendocrine carcinomas, particularly in the setting of carcinomas of the lung, where this distinction is most critical.…”
Section: Identification Of Neuroendocrine Tumorsmentioning
confidence: 99%
“…SCLC is clearly associated with neuroendocrine properties such as dense core granules on electron microscopy, and the presence of Ldopa decarboxylase activity, neuron-specific enolase, creatine kinase-BB or gastrin-releasing peptide on cell cul tures [8], Immunohistochemical staining of SCLC has shown positive results for NSE in 70-100%, and for chromogranin A in 40% [8][9][10][11]. On the other hand, it has been demonstrated that up to 30% of cell lines or fresh tis sue obtained from patients with NSCLC show features of neuroendocrine differentiation, in particular the expres sion of NSE [11][12][13][14], The clinical relevance of this neu roendocrine differentiation in NSCLC is not yet clearly understood. In several studies it has been suggested that the clinical behavior of neuroendocrine NSCLC may re semble SCLC tumors [5,7,14].…”
Section: Introductionmentioning
confidence: 99%
“…In these, surgery asacurative measure and the value of adjuvant chemotherapeutic re gimens may be questioned, as only modest results are ob tained [3], Only a subgroup of NSCLC may benefit by chemotherapy, and it is not possible to identify these pa tients by the usual clinical procedures [4], Recently atten tion has focused on the relationship between biological factors within tumor cells and differences in tumor beha vior or clinical features [5][6][7]. SCLC is clearly associated with neuroendocrine properties such as dense core granules on electron microscopy, and the presence of Ldopa decarboxylase activity, neuron-specific enolase, creatine kinase-BB or gastrin-releasing peptide on cell cul tures [8], Immunohistochemical staining of SCLC has shown positive results for NSE in 70-100%, and for chromogranin A in 40% [8][9][10][11]. On the other hand, it has been demonstrated that up to 30% of cell lines or fresh tis sue obtained from patients with NSCLC show features of neuroendocrine differentiation, in particular the expres sion of NSE [11][12][13][14], The clinical relevance of this neu roendocrine differentiation in NSCLC is not yet clearly understood.…”
Section: Introductionmentioning
confidence: 99%